Dephosphorylation of myo-inositol phosphates in the in vitro intestinal Caco-2 cell model. (2nd January 2018) - Briviba, Karlis; Schollenberger, Margit; Rodehutscord, Markus; Greiner, Ralf
Abstract: Plant and microbial phytases present in raw materials can cause a dephosphorylation of phytate ( myo -inositol hexakisphosphate) (InsP6 )) during food processing resulting in a broad range of different myo -inositol phosphates such as pentakisphosphate (InsP5 ) and tetrakisphosphate (InsP4 ) in foods. Here, we investigated whether the human intestinal epithelium is able to dephosphorylate myo -inositol phosphates (InsP6, InsP5 -, InsP4 -, InsP3 -isomers) using an in vitro model with differentiated human Caco-2 cells cultured on semipermeable inserts. Incubation of InsP6 and an InsP5 -isomer with cells for 3 h showed no dephosphorylation of both InsPs. Treatment of cells with a mixture of different InsP4 -isomers, however, caused a formation of about 3.5% of an InsP3 -isomer (Ins(1, 5, 6)P3 ) and treatment with a mixture of different InsP3 -isomers caused about 20% formation of InsP2 -isomers, respectively. Thus, human intestinal cells can contribute to the dephosphorylation of myo -inositol phosphates of partly dephosphorylated forms such as InsP3 and InsP4 . Graphical Abstract: